2013
DOI: 10.3389/fncel.2013.00076
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin 5-HT3 receptor: a novel neurodevelopmental target

Abstract: Serotonin (5-hydroxytryptamine, 5-HT), next to being an important neurotransmitter, recently gained attention as a key-regulator of pre- and postnatal development in the mammalian central nervous system (CNS). Several receptors for 5-HT are expressed in the developing brain including a ligand-gated ion channel, the 5-HT3 receptor. Over the past years, evidence has been accumulating that 5-HT3 receptors are involved in the regulation of neurodevelopment by serotonin. Here, we review the spatial and temporal exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 96 publications
1
34
1
Order By: Relevance
“…5-HT 3 and 5-HT 6 are proposed as candidates to modulate neural migration (30). Although we observed an effect of 5-HT 6 but not 5-HT 3 on PC12 migration, it is possible 5-HT 3 also modulated the PC12 cell migration in different conditions, such as in the presence of NGF.…”
Section: Insensitivity Of 5-ht 3 In Undifferentiated Pc12 Cellscontrasting
confidence: 44%
“…5-HT 3 and 5-HT 6 are proposed as candidates to modulate neural migration (30). Although we observed an effect of 5-HT 6 but not 5-HT 3 on PC12 migration, it is possible 5-HT 3 also modulated the PC12 cell migration in different conditions, such as in the presence of NGF.…”
Section: Insensitivity Of 5-ht 3 In Undifferentiated Pc12 Cellscontrasting
confidence: 44%
“…Human 5-HT 3 Rs are thought to play a role in gastrointestinal function, in nociception, neurodevelopment, and in a variety of psychiatric disorders (Lummis, 2012;Engel et al, 2013;Thompson, 2013). As a consequence, they are important targets for therapeutic drug discovery.…”
mentioning
confidence: 99%
“…PET studies on Rhesus monkeys have revealed that clinically relevant doses of Atomoxetine, the treatment drug for depression and ADHD, are capable of occupying both NET and SERT upto a range of >85% for SERT in a dose-dependent manner (Ding YS et al, 2014). 5-HTR3A controls neuronal migration and 5-HTR6 regulate dendritic differentiation (Engel et al, 2013). 5-HTR3…”
Section: Origin Of Serotonergic Hypothesis In Adhdmentioning
confidence: 99%